Interaction between MYC2 and ETHYLENE INSENSITIVE3 Modulates Antagonism between Jasmonate and Ethylene Signaling in Arabidopsis . Issue 1 (7th January 2014) - Song, Susheng; Huang, Huang; Gao, Hua; Wang, Jiaojiao; Wu, Dewei; Liu, Xili; Yang, Shuhua; Zhai, Qingzhe; Li, Chuanyou; Qi, Tiancong; Xie, Daoxin
Abstract : The authors reveal a mechanism underlying jasmonate (JA) and ethylene (ET) antagonism: Interaction between the JA-activated transcription factor MYC2 and the ET-stabilized transcription factor EIN3, reciprocally repressing their transcriptional activity, modulates the antagonistic actions of JA and ET in regulating apical hook curvature, wound-responsive gene expression, and defense against insect attack. Abstract: Plants have evolved sophisticated mechanisms for integration of endogenous and exogenous signals to adapt to the changing environment. Both the phytohormones jasmonate (JA ) and ethylene (ET ) regulate plant growth, development, and defense. In addition to synergistic regulation of root hair development and resistance to necrotrophic fungi, JA and ET act antagonistically to regulate gene expression, apical hook curvature, and plant defense against insect attack. However, the molecular mechanism for such antagonism between JA and ET signaling remains unclear. Here, we demonstrate that interaction between the JA -activated transcription factor MYC2 and the ET -stabilized transcription factor ETHYLENE-INSENSITIVE3 (EIN3) modulates JA and ET signaling antagonism in Arabidopsis thaliana . MYC2 interacts with EIN3 to attenuate the transcriptional activity of EIN3 and repress ET -enhanced apical hook curvature. Conversely, EIN3 interacts with and represses MYC2 to inhibit JA -induced expression of wound-responsive genes and herbivory-inducible genes and to attenuate JA -regulated plant defense against generalist herbivores. Coordinated regulation of plant responses in both antagonistic and synergistic manners would help plants adapt to fluctuating environments.